The Relationship Between Self-Efficacy and Anxiety Among Rehabilitants at the BNN Rehabilitation Center in Tanah Merah, East Kalimantan - Arief Budiman; Sevia Dewi Ningtiyas (INDOGENIUS, 2026)
Background & Objective: Narcotics are substances or drugs derived from plants or non-plants, either synthetic or semi-synthetic. Narcotics can cause decreased consciousness, drowsiness, loss of sensation, and may also reduce or eliminate pain. However, they can lead to dependence and are classified into several categories based on their properties and effects. The purpose of this study is to determine the relationship between self-efficacy and anxiety among rehabilitation patients. Method: This research uses a quantitative design with a cross-sectional approach, the number of respondents in this study was 89 rehabilitant at the BNN Rehabilitation Center in Tanah Merah East Kalimantan . By distributing questionnaires which will later be filled in by respondents and data processing will beb carried out using the SPSS version 27 application to test correlation. Result: The results obtained from the p-value of the relationship between self-efficacy and anxiety are 0.961 < 0.05. The conclusion is that there is no relationship between self-efficacy and anxiety in rehabilitation, as follows high self-efficacy 69.7% and no anxiety 50.6%. Conclusion: This study concludes that there is no significant relationship between self-efficacy and anxiety among rehabilitation patients. Although most respondents demonstrated high self-efficacy (69.7%) and no anxiety (50.6%), the findings indicate that self-efficacy does not have a direct influence on the level of anxiety in this population. Other factors, such as environmental support, coping mechanisms, or duration of rehabilitation, may play a more substantial role in influencing anxiety levels. Further research is recommended to explore these contributing factors in greater depth.